데이터경제 개념화 및 생태계 구축에 관한 연구: 우리나라의 부동산∙의료∙금융부문을 중심으로 - 조만; 문성욱; 이인복 (KDI School of Public Policy and Management, 2021)
본 연구의 목적은 ‘데이터경제’의 개념화 및 활성화 방안을 우리나라의 3개 서비스부문(금융∙부동산∙의료)에 초점을 맞추어 분석하는데 있다. 이를 위하여 최근 국내외 데이터 경제 관련 문헌의 주요 논거를 정리하였고, 2개의 국제학술논문 데이터베이스를 이용하여 상기 3개 부문의 데이터경제 관련 논문을 추출하여 메타분석을 수행하였다: 미국 국립보건원(NIH)의 ‘PubMed’로부터 추출한 263,974건의 보건∙의료 분야 학술논문; 그리고 WOS(Web of Science)로부터 추출한 26,859건의 금융∙부동산 분야 학술논문이 포함됨. 분석결과를 요약하면, 데이터경제는 디지털 데이터의 구축∙공유∙분석∙활용을 통하여 지역 또는 국가 차원의 사회적 후생을 증가시키는 혁신생태계로 정의하였고, 이의 핵심 구성 요소는 DPA(Data∙Platform∙AI) 기반의 하부구조와 제반 촉진기제들이 포함된다. 최근 문헌에서 논의되고 있는 데이터경제의 경제∙사회적 기대효과는 다음 3개 유형으로 정리하였고 - (1) 플랫폼 효과; (2) 예측력 증대 효과; (3) 새로운 분석기법 효과, 이들이 3개 서비스부문에 주는 시사점을 논의하였다. 메타분석의 결과는 3개 부문의 데이터경제 관련 학술논문이 2015년경부터 폭발적인 증가추세에 있고, 공저자의 숫자 및 다국간 협력논문의 비중이 지속적으로 증가하는 것을 보여 주었다. 우리나라의 경우 논문의 양적인 측면에서는 대체로 양호한 것으로 판단되나 (2개 DB 모두에서 세계 8위를 기록), 질적인 측면에서는 경쟁 상대국에 비하여 상당히 뒤쳐져 있는 것으로 나타났다 (평균 인용횟수, 연구주제의 참신성 측면에서). 상기 분석결과를 기초로 우리나라 3개 부문에서의 데이터경제 활성화를 위한 제반 정책과제를 논의하였다. The main objective of this study is to conceptualize “data economy (DE)” and to assess the current state of fostering its ecosystem in three particular service sectors in Korea – finance, real estate, and health care. To that end, we, first, synthesize the key arguments advanced in the recent literature as to the expected socio-economic effects of DE and, second, perform the meta-analyses based on the academic articles of relevancy that are extracted from two international databases: 263,974 articles in the fields of health and medical science from PubMed, established by the National Institute of Health of the U.S.; and, 26,859 articles in the fields of finance and real estate from Web of Science (WOS). Our results are summarized as: for our analytical purpose, DE is defined as an innovation ecosystem in which digital data is collected∙shared∙analyzed∙utilized such that regional or national welfare gain can be realized; Its key elements include DPA(Data∙Platform∙AI)-driven infrastructure along with various enablers, both market-driven and institution-driven; The expected effects of DE, as discussed in the literature, are categorized into three types – (1) the platform effect, (2) the prediction power effect, and (3) the new analytics effect, whose implications to the three sectors are also elaborated; According to the metaanalyses performed, the DE-related academic studies have been growing in an explosive phase in all three sectors since around 2015, and the trend of increasing co-authorship and inter-country collaboration is also observed; And, those articles written by the Korean authors (according to their affiliations) show a fair standing in terms of the quantity, i.e., number of articles (8th place in both databases) but are being lagged significantly compared to other advanced economies in terms of the quality (e.g., average number of citations, newness of research topics). Using the above findings, we discuss the policy directions and tasks for activating DE and expanding its social effects in the three sectors examined.